Layerable Apps: Comparing Concurrent and Exclusive Display of Augmented Reality Applications - Huynh, Brandon; Wysopal, Abby; Ross, Vivian; Orlosky, Jason; Hollerer, Tobias (2022 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2022)
Current augmented reality (AR) interfaces are often designed for interacting with one application at a time, significantly limiting a user's ability to concurrently interact with and switch between multiple applications or modalities that could run in parallel. In this work, we introduce an application model called Layerable Apps, which supports a variety of AR application types while enabling multitasking through concurrent execution, fast application switching, and the ability to layer application views to adjust the degree of augmentation to the user's preference. We evaluated Layerable Apps through a within-subjects user study (n=44), compared against a traditional single-focus application model on a split-information task involving the simultaneous use of multiple applications. We report the results of our study, where we found differences in quantitative task performance, favoring Layerable mode. We also analyzed app usage patterns, spatial awareness, and overall preferences between both modes as well as between experienced and novice AR users.